Effect of young basketball players’ self-regulation on their psychological indicators - Rochniak, Anton; Kostikova, Ilona; Fomenko, Karyna; Khomulenko, Tamara; Arabadzhy, Tymur; Viediernikova, Tetiana; Diomidova, Nataliia; Kramchenkova, Vera; Scherbakova, Olena; Kovalenko, Marta; Kuznetsov, Oleksiy (My University, 2020)
One of the most important factors in the success of sports activities is the level of psychological readiness. The most significant indicator of psychological readiness is the ability to qualitatively regulate athlete’s activity, behavior, and mental state by their own psychic means (i.e., the ability to selfregulate). At the same time, there is not enough insightful research in sports science and in this area of knowledge.To determine the nature of the relationship and links between the psychological characteristics of young basketball players and the specific features of their self-regulation. A total of 160 basketball players (15-20 years old) participated in the study. The methods of selfregulation of sports activity, dispositional state of flow, basic beliefs, and dispositive optimism were used. Correlation links between the indicators of self-regulation of sports activities and the indicators of dispositional state of flow, basic beliefs, and dispositive optimism were revealed. The most significant link was defined with self-inductance and identified regulation. The differences between young basketball players with different peculiarities of self-regulation of sports activity were determined by almost all indicators of the dispositional state of flow, basic beliefs, and dispositive optimism. It was confirmed that the specificity of self-regulation of young basketball players is connected with the peculiarities of the dispositional state of flow, dispositional optimism, and basic beliefs. Through comparison, it is determined that young basketball players with autonomous sports self-regulation have the advantage of almost all indicators of the dispositional state of flow and they have more optimistic views on the future.
Keywords: dispositional state of flow; optimism; typological profiles; features; mental